Acute postoperative pain relief with immediate-release tapentadol: randomized, double-blind, placebo-controlled study conducted in South Korea. (December 2014) - Lee, Y. K.; Ko, J. S.; Rhim, H. Y.; Lee, E. J.; Karcher, K.; Li, H.; Shapiro, D.; Lee, H. S.
Abstract Objective: To broaden the ethnic groups in which tapentadol IR is evaluated for treating acute postoperative pain to include Asians. Methods: In this phase 3, multicenter, double-blind, randomized study, 352 Korean adults with moderate-to-severe pain following hallux valgus surgery received tapentadol IR 50 or 75 mg or placebo orally every 4–6 hours for 72 hours. Patients requesting other (rescue) analgesics during this period were discontinued for lack of efficacy. The primary endpoint, sum of pain intensity difference (SPID) over 48 hours, was evaluated based on the difference between tapentadol IR and placebo in least squares (LS) mean change from baseline using analysis of covariance (ANCOVA). Secondary endpoints included the time to first rescue medication use and the distribution of responder rates. Results: A treatment effect, favoring tapentadol IR, was observed for SPID48 (p < 0.001 for both doses vs. placebo, ANCOVA). The between-group difference (vs. placebo) in LS means of SPID48 was 76.4 (95% CI: 51.0, 101.7) for tapentadol IR 50 mg and 90.6 (95% CI: 65.1, 116.1) for tapentadol IR 75 mg. Time to first rescue medication use was delayed for tapentadol IR (p < 0.001 for both doses vs. placebo; log-rank test). The distribution of responders at 12, 24, 48, and 72 hours favored tapentadol IR (p ≤ 0.001 for both doses vs. placebo; Cochran–Mantel–Haenszel test). Dizziness, nausea, and vomiting were each reported in ≥10% tapentadol-treated patients and at an incidence ≥2-fold higher vs. placebo. The study findings may be limited by study drug dosing every 4 to 6 hours and frequent monitoring during treatment, neither of which mimic pain treatment in clinical practice. However, any potential bias based on this systematic monitoring of patients would be mitigated by the randomized, double-blind nature of the study, with all treatment groups similarly affected by such biases, if any. Conclusions: Tapentadol IR reduced acute pain intensity, significantly more than placebo, after orthopedic surgery in Korean patients. Clinical trial registration: NCT01516008.